2010
DOI: 10.1093/pasj/62.4.879
|View full text |Cite
|
Sign up to set email alerts
|

Internal Fine Structure of Ellerman Bombs

Abstract: We conducted coordinated observations of Ellerman bombs (EBs) between Hinode Satellite and Hida Observatory (HOP12). Ca II H broad-band filter images of NOAA 10966 on 2007 August 9 and 10 were obtained with the Solar Optical Telescope (SOT) aboard the Hinode Satellite, and many bright points were observed. We identified a total of 4 bright points as EBs, and studied the temporal variation of their morphological fine structures and spectroscopic characteristics. With high-resolution Ca II H images of SOT, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 23 publications
5
38
0
Order By: Relevance
“…In both lines the slab is thick for the target parameters, but overlying cooler fibrils are yet thicker so that only wing brightenings result, at smaller moustache extent then for Hα since these lines suffer no A124, page 10 of 13 Stark broadening. This is also conform observations (Paper II for Ca ii 8542 Å, Hashimoto et al 2010 for Ca ii H).…”
Section: Lte Extinction Of Eb Diagnosticssupporting
confidence: 93%
See 2 more Smart Citations
“…In both lines the slab is thick for the target parameters, but overlying cooler fibrils are yet thicker so that only wing brightenings result, at smaller moustache extent then for Hα since these lines suffer no A124, page 10 of 13 Stark broadening. This is also conform observations (Paper II for Ca ii 8542 Å, Hashimoto et al 2010 for Ca ii H).…”
Section: Lte Extinction Of Eb Diagnosticssupporting
confidence: 93%
“…In the outer Hα wings surrounding cool gas lacks moustache opacity from shortage of free electrons for Stark broadening. The therefore unmolested Hα-moustache sharpness permits, at sufficiently high angular resolution, to resolve very fine substructure within EBs, as observed in Hashimoto et al (2010) and Paper I.…”
Section: Lte Extinction Of Eb Diagnosticsmentioning
confidence: 89%
See 1 more Smart Citation
“…Ellerman bombs have been observed in the Ca ii H line by Hashimoto et al (2010). We probe the diagnostic potential of the Ca ii H line profile to identify and study EBs.…”
Section: Caii H Line: An Ideal Tracer Of Ebsmentioning
confidence: 96%
“…These studies showed that EBs exhibit enhanced brightenings not only in the wing of the Hα line, but also in the wings of the Ca ii IR line. Traces of EBs were also observed in the ultraviolet (UV) continuum at 160 nm (Qiu et al 2000;Pariat et al 2007), while Hashimoto et al (2010) observed EBs in the Ca ii H line.…”
Section: Introductionmentioning
confidence: 96%